Case Report: Fatal Outcome for a Preterm Newborn With Meningitis Caused by Extended-Spectrum β-Lactamase-Producing Escherichia coli Sequence Type 1193 - Oldendorff, Frida; Linnér, Agnes; Finder, Mikael; Eisenlauer, Peter; Kjellberg, Malin; Giske, Christian G.; Nordberg, Viveka (Frontiers in Pediatrics, 2022)
Introduction: In this case report, we describe an extended-spectrum -lactamase (ESBL) – E. coli strain of sequence type (ST) 1193, a novel, virulent, multidrug-resistant (MDR) clone with a rapid global spread. ST 1193 has been more commonly associated with invasive disease than other ESBL-E.coli STs. To our knowledge, this is the first known case in Sweden where a newborn died of an ESBL-E. coli ST 1193 meningitis. We emphasize that the clinical knowledge about the properties of certain MDR-clones should be increased. Case Report: A moderately preterm boy was born after preterm prolonged rupture of membranes. The mother had an ESBL-E. coli urinary tract infection during pregnancy. At 36 hours he developed signs of infection and was given first-line therapy for early onset sepsis. Thereafter he developed seizures. The treatment was changed to cover suspected meningitis. Culture showed growth of the same ESBL- E.coli ST 1193 strain in the child’s blood and cerebrospinal fluid, as well as in the mother's urine. Antibiotics were adapted. His condition deteriorated and he developed fulminant septic shock with treatment-resistant seizures. The boy passed away at three days of age. Conclusion: This case highlights the risk of delay in diagnosis when a marking for carriage of MDR-bacteria is falsely removed from a medical record of a pregnant women. Further, it demonstrates that ESBL-E. coli ST 1193 infection in neonates can be fatal. Thus, studies regarding virulence factors of ESBL-E.coli infections in pregnant women and their children are needed in order to understand the association between this infection and severe invasive disease in newborn children.